Effects of mindfulness exercises as stand-alone intervention on symptoms of anxiety and depression: systematic review and meta-analysis - Blanck, Paul; Perleth, Sarah; Kröger, Paula; Ditzen, Beate; Bents, Hinrich; Mander, Johannes (Behaviour research and therapy, 2018)
Mindfulness-based interventions (MBIs) are currently well established in psychotherapy with meta-analyses demonstrating their efficacy